Utilization of FilmArray Gastrointestinal Panel (GIP) Results on Altering Empiric Antibiotic (ABX) Use in Patients with Acute Diarrhea. (4th October 2017) - Raux, Brian R; Aldhaeefi, Mohammed; Steed, Lisa L; Bosso, John
Abstract: Background: Acute infectious diarrhea is a leading cause of hospitalizations, outpatient visits, and lost quality of life in the United States. Rapid diagnostic technology may provide an opportunity to quickly optimize ABX therapy for acute infectious diarrhea. The GIP is a multiplex PCR test that detects 13 bacteria, 5 viruses, and 4 parasites in approximately 1 hour of run time. Our objective was to determine the frequency of alterations in empiric ABX therapy for acute diarrhea within 48 hours of reporting of GIP results. Methods: Patients that had the GIP performed on diarrheagenic stool while in our emergency department or an inpatient location from January 1 to June 30, 2016 were identified. Patient data, including gender, race, age, ABX use and duration, and the results of non-stool bacterial cultures (if obtained) were collated with GIP results. Results: Complete patient information and GIP results were available on 517 patients. At least 1 positive result occurred in 220 patients; 45 patients (8.7%) had ≥ 2 positive results. There were 161, 73, and 2 positive results for bacteria, viruses, and parasites, respectively. Clostridium difficile ( n = 99) was most commonly identified and it was the only organism identified in 80 patients. Within 48 hours of result availability in the medical record, ABX were added in 47.3% of patients with any positive result and 24.2% of patients with negative results. Empiric ABX were stopped in 42.9 and 48.6% of patients with positive or negative results, respectively. ABX were altered (ie, start, stop, dose change) in 55.9 and 38.4% of patients with positive or negative results, respectively. Conclusion: GIP results appear to impact changes in ABX therapy, though these may not have been the sole driver of change in all cases. That there may be room for improvement suggests an opportunity for antimicrobial stewardship (AST) initiatives, such as prospective auditing of GIP results by AST staff who make recommendations to the treatment team, or an expansion of our current gastroenteritis guidelines to include a clinical pathway for all organisms on the GIP to decrease inappropriate ABX use. Disclosures: All authors: No reported disclosures.